Meningioma of Lumbar Localization in a Patient with Human Immunodeficiency Virus - Jorge Luis Acevedo Cardoso; Yoniel Suárez Guerrero; Samuel Sánchez Sánchez (Revista Finlay, 2017)
Cauda equine meningiomas are neoplasms of mesodermal origin and generally of benign behavior. They originate from the meningothelial cells that make up the arachnoid villi. A case of a 37 year old patient with low back pain of one year of evolution is presented. On physical examination there was decreased muscular strength and hypoesthesia in lower limbs. In nuclear magnetic resonance, a rounded isointense image was observed within the medullar canal at L2 level. At preoperative checkup the human immunodeficiency virus test was positive. Antiretroviral treatment was started and after six months, surgery was performed, the biopsy reported a meningothelial meningioma. The evolution of the patient was favorable. The aim of the present study is to describe this tumor presentation in a patient diagnosed with human immunodeficiency virus.